Terrestrial Mollusks as Chronological Records in Brazilian Shellmounds. Issue 5 (2nd May 2017) - Macario, Kita D; Tenório, Maria Cristina; Alves, Eduardo Q; Oliveira, Fabiana M; Chanca, Ingrid S; Netto, Bruna; Carvalho, Carla; Souza, Rosa; Aguilera, Orangel; Guimarães, Renato B
Abstract: Among other zooarchaeological remains, terrestrial snails' shells from the Thaumastus and Megalobulimus genera are found in some Brazilian shellmounds, presenting a potential substitute for charcoal in radiocarbon dating analyses, as reliable representatives of the atmospheric carbon isotopic ratio. In this paper, we present statistically similar results of both charcoal and land snails samples from the same archaeological contexts in three settlements on the coast of Rio de Janeiro. The Manitiba I shellmound results range from 4.2 to 3.7 ka cal BP (95.4%), contemporary with the Saquarema shellmound, occupied during the period from 4.3 to 3.6 ka cal BP (95.4%). For the Usiminas shellmound, two groups of samples revealed different periods of time for two occupational layers from 2.3 to 2.1 ka cal BP (95.4%) and from 1.6 and 1.3 ka cal BP (95.4%). A model constraining each group of samples to within a single phase has a general agreement of 97% with only two outliers out of 22 dates, yielding minimum individual agreement of 74% and 7% posterior outlier probability for Saquarema shells. These are good examples of sites in which the occupation chronology can be successfully obtained by the radiocarbon dating of land snails.